Review Article: Philipp Niewöhner (επιμ.), The Archaeology of Byzantine Anatolia. From the Late Antiquity until the Coming of the Turks, Οξφόρδη 2017 - ΤΣΙΒΙΚΗΣ Νίκος (Byzantina Symmeikta, 2020)
Philipp Niewöhner (επιμ.), The Archaeology of Byzantine Anatolia. From the Late Antiquity until the Coming of the Turks, Οξφόρδη 2017